(untitled) (The Journal of Geography Education in Africa, 2022)
The Iziko Museums of South Africa are a group of 11 museums located in Cape Town. This article provides an overview of possible applications of geo-literacy in a museum context. The use of geographical tools in exhibitions and educational programmes at the museum is evaluated with reference to place, spatial processes, spatial distribution patterns, and human-environment interactions. The museums’ collections, research activities and exhibitions can support the school curriculum and also enhance cultural sensitivity, stimulate dialogue, and encourage problemsolving. The activities at the Iziko Museums of South Africa have the potential to enhance and support the development of personal responsibility to learn from the past and contribute to creating a better future for all. Museum educators and curators should therefore further explore and implement strategies to include geo-literacy when developing exhibitions and educational programmes in their unique context.